STEM-PjBL Learning through Seblak Rafael Project to Increase Students’ Science Literacy on the Topic of Heat and Temperature - Ana Widya Ilahi; Irma Rahmawati (CV. Gerasi Insan Nusantara, 2026)
The Program for International Student Assessment (PISA) has released the results of the 2022 ranking, where the average score of Indonesian students' scientific literacy skills has decreased. The results of a preliminary study at SMAN 5 Banjarbaru showed that one of the factors in the decline in scientific literacy was the lack of student participation in physics learning because it was considered difficult by students. To overcome this problem, project-based learning (PjBL) was implemented with STEM integration through viral food on social media called Seblak Rafael. The purpose of this study was to describe the implementation of STEM-PjBL learning through the Seblak Rafael project and the increase in students' scientific literacy after participating in the learning. This study used a mixed method with an Embedded Design. The research subjects consisted of 39 eleventh grade students. Data on the implementation of STEM-PjBL learning through the Seblak Rafael project were obtained through observation which was then subjected to descriptive analysis. Scientific literacy data were obtained through tests with reasoned multiple-choice questions which were then analyzed for improvement using N-gain. The results of the study showed that the implementation of STEM-PjBL learning through the Seblak Rafael project obtained a percentage of 87% in the very good category with the stages of starting with the essential question, designing a plan for the project, creating a schedule, monitoring the student and the progress of the project, assessing the outcome, evaluating the experience. The increase in students' scientific literacy through this learning obtained an N-Gain value of 0.53 which is included in the moderate criteria.